Practitioners' views on the effects of the “For caring supervised visitation in child welfare” training - Joly, Marie-Pierre; Blais, Marie-France; Poirier, Marie-Andrée; Gervais, Mathieu-Joel; Soto Duran, Mauricio (Child abuse & neglect, 2022)
In youth protection, the supervision of visits between children and their parent(s) with whom they no longer live is a complex clinical practice. The “For Caring Supervised Visitation in Child Welfare” training was designed to equip workers on the subject. The training was developed in Quebec (Canada), based on a co-construction approach (clinical and scientific) of knowledge and a rigorous pedagogical engineering methodology. This article presents the results of a research study that sought to explore the perceived impact of the training, from the worker's perspective. Semi-directed interviews were conducted with 20 workers who had completed the training. A thematic analysis of the full content of the interviews was carried out (Braun & Clarke, 2006). This project has produced initial exploratory findings that the training has made it possible to develop a more rigorous analysis of the need for supervision, better planning of visits, greater uniformity of practices among workers and adoption of practices that promote parental engagement. According to workers, these effects of the training are influenced by factors such as time devoted solely to training in the schedule, a workload adapted to the practice to be put in place and sufficient support from managers and organization. These results suggest that training improves practices in the context of supervised visits. To maximize these benefits, it is suggested that workers benefit from ongoing clinical support and adequate practice conditions.